1998
DOI: 10.2307/3433921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Micronutrients on Metal Toxicity

Abstract: There is growing evidence that micronutrient intake has a significant effect on the toxicity and carcinogenesis caused by various chemicals. This paper examines the effect of micronutrient status on the toxicity of four nonessential metals: cadmium, lead, mercury, and arsenic. Unfortunately, few studies have directly examined the effect of dietary deficiency or supplementation on metal toxicity. More commonly, the effect of dietary alteration must be deduced from the results of mechanistic studies. We have cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 71 publications
3
84
1
7
Order By: Relevance
“…Hence, calcium insufficiency could intensify the harmful effects of lead on child growth, as gastrointestinal lead absorption is the major pathway of its uptake. 33 We found that blood lead levels during late pregnancy affected postnatal growth at 24 months. The early programming of postnatal growth caused by intrauterine exposure to lead may result from the separate influence of maternal blood lead levels either during the early or late gestational period.…”
Section: Figurementioning
confidence: 82%
“…Hence, calcium insufficiency could intensify the harmful effects of lead on child growth, as gastrointestinal lead absorption is the major pathway of its uptake. 33 We found that blood lead levels during late pregnancy affected postnatal growth at 24 months. The early programming of postnatal growth caused by intrauterine exposure to lead may result from the separate influence of maternal blood lead levels either during the early or late gestational period.…”
Section: Figurementioning
confidence: 82%
“…Fruit was the third most energy source in their diet and provided important micronutrients. A protective effect of fruit against mercury contamination, via phytochemicals able to interact with the absorption, excretion and transport of toxic metals, has been postulated (Peraza et al, 1998). Fruit supplies vitamins C and E that possess anti-oxidant properties and may neutralize the toxic effects of mercury (Jacob-Ferreira et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Adequate intake of copper provides protection against lead, whereas higher intake of copper increases lead absorption [124][125][126][127] . The above studies clearly suggest that these micronutrients play a role in preventing toxic metal absorption and could also be co-administered during chelation therapy to maintain essential metal status during chelation treatment and could serve a dual purpose; i) to prevent possible essential metal deficiency syndrome and ii) to accelerate lead elimination due to their own antagonistic/biochemical/pharmacological effects 128,163) . A beneficial role of zinc supplementation during lead chelation therapy has been reported 15,129) .…”
Section: Coppermentioning
confidence: 99%